Realignment Surgery for Failed Osteochondral Autologous Transplantation in Osteochondral Lesions of the Talus Associated With Malalignment - Jaeyoung Kim MD; Jesse Seilern und Aspang; Kim Ji-Beom MD; Jonathan Day MD; Oliver Gagné MD; Woo-Chun Lee MD (Foot & Ankle Orthopaedics, 2022)
Category: Ankle Arthritis; Sports Introduction/Purpose: While osteochondral autograft transplantation (OAT) offers favorable results in most patients with osteochondral lesions of the talus (OLT), some patients continue to experience persistent pain following the procedure. Information regarding the etiology of this pain and outcomes of revision surgery are limited. This study aimed to report results of revision surgery with realignment procedures in patients with failed OAT who demonstrated concomitant malalignment at the distal tibia or hindfoot. Methods: Eight ankles with persistent pain following OAT underwent revision surgery with realignment procedures. All patients underwent primary OAT for treatment of medial OLTs. Patients were divided into two groups based on the main location of deformity; the Supramalleolar realignment group (SRG, five ankles) and the Hindfoot realignment group (HRG, three ankles). No direct procedure was performed on the osteochondral lesion at the time of revision surgery. Ankle and hindfoot alignment were evaluated using six parameters in weightbearing radiographs. Computed tomography (CT) was used to assess for medial gutter narrowing, spur formation, and cyst volume around transplanted osteochondral plug pre-and postoperatively. Clinical outcomes were assessed using foot function index and visual analogue scale. Results: All patients had medial gutter narrowing or spur formation, which are early signs of ankle arthritis. The SRG had varus distal tibial alignment with a median medial distal tibial angle of 85.7 degrees (Interquartile range [IQR], 3.2). The HRG had valgus hindfoot alignment and a lower medial longitudinal arch with a median hindfoot moment arm of 8.4 mm (IQR, 6.1) and a median Meary angle of 11.8 degrees (IQR, 1.4). Spontaneous restoration of the osteochondral lesion was observed after realignment surgery, with cyst volume decreasing from 0.2592cm3 to 0.0873cm3 (p<0.05, Figure 1 and Figure 2). Clinical scores improved in all patients. Conclusion: The current study shows the effectiveness of realignment surgery in a selected patient group in whom OAT has failed. Our study provides evidence for the role of realignment procedures in these cases, with results suggesting improved patient-reported outcomes and spontaneous restoration of osteochondral lesions.